Recent Research Advances in Nano-Based Drug Delivery Systems for Local Anesthetics - Ma H; Pan Z; Lai B; Zan C; Liu H (Drug Design, Development and Therapy, 2023)
He Ma,1 Zhenxiang Pan,1 Bingjie Lai,2 Chunfang Zan,3,4 He Liu5 1Department of Anesthesiology, The Second Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Intensive Care Unit, The Second Hospital of Jilin University, Changchun, People’s Republic of China; 3Department of Nuclear Medicine, First Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 4Collaborative Innovation Center for Molecular Imaging of Precision Medicine, Shanxi Medical University, Taiyuan, People’s Republic of China; 5Department of Orthopedics, The Second Hospital of Jilin University, Changchun, People’s Republic of ChinaCorrespondence: He Liu, Department of Orthopedics, The Second Hospital of Jilin University, Changchun, 130041, People’s Republic of China, Email heliu@jlu.edu.cnAbstract: From a clinical perspective, local anesthetics have rather widespread application in regional blockade for surgery, postoperative analgesia, acute/chronic pain control, and even cancer treatments. However, a number of disadvantages are associated with traditional local anesthetic agents as well as routine drug delivery administration ways, such as neurotoxicity, short half-time, and non-sustained release, thereby limiting their application in clinical practice. Successful characterization of drug delivery systems (DDSs) for individual local anesthetic agents can support to achieve more efficient drug release and prolonged duration of action with reduced systemic toxicity. Different types of DDSs involving various carriers have been examined, including micromaterials, nanomaterials, and cyclodextrin. Among them, nanotechnology-based delivery approaches have significantly developed in the last decade due to the low systemic toxicity and the greater efficacy of non-conventional local anesthetics. Multiple nanosized materials, including polymeric, lipid (solid lipid nanoparticles, nanostructured lipid carriers, and nanoemulsions), metallic, inorganic non-metallic, and hybrid nanoparticles, offer a safe, localized, and long-acting solution for pain management and tumor therapy. This review provides a brief synopsis of different nano-based DDSs for local anesthetics with variable sizes and structural morphology, such as nanocapsules and nanospheres. Recent original research utilizing nanotechnology-based delivery systems is particularly discussed, and the progress and strengths of these DDSs are highlighted. A specific focus of this review is the comparison of various nano-based DDSs for local anesthetics, which can offer additional indications for their further improvement. All in all, nano-based DDSs with unique advantages provide a novel direction for the development of safer and more effective local anesthetic formulations.Keywords: local anesthetics, pain, drug delivery system, nanotechnology, nanocarriers, nanoparticles